Metagenome Assembled Genome of a Novel Verrucomicrobial Methanotroph From Pantelleria Island - Picone, Nunzia; Blom, Pieter; Hogendoorn, Carmen; Frank, Jeroen; van Alen, Theo; Pol, Arjan; Gagliano, Antonina L.; Jetten, Mike S. M.; D’Alessandro, Walter; Quatrini, Paola; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2021)
Verrucomicrobial methanotrophs are a group of aerobic bacteria isolated from volcanic environments. They are acidophiles, characterized by the presence of a particulate methane monooxygenase (pMMO) and a XoxF-type methanol dehydrogenase (MDH). Metagenomic analysis of DNA extracted from the soil of Favara Grande, a geothermal area on Pantelleria Island, Italy, revealed the presence of two verrucomicrobial Metagenome Assembled Genomes (MAGs). One of these MAGs did not phylogenetically classify within any existing genus. After extensive analysis of the MAG, we propose the name of “Candidatus Methylacidithermus pantelleriae” PQ17 gen. nov. sp. nov. The MAG consisted of 2,466,655 bp, 71 contigs and 3,127 predicted coding sequences. Completeness was found at 98.6% and contamination at 1.3%. Genes encoding the pMMO and XoxF-MDH were identified. Inorganic carbon fixation might use the Calvin-Benson-Bassham cycle since all genes were identified. The serine and ribulose monophosphate pathways were incomplete. The detoxification of formaldehyde could follow the tetrahydrofolate pathway. Furthermore, “Ca. Methylacidithermus pantelleriae” might be capable of nitric oxide reduction but genes for dissimilatory nitrate reduction and nitrogen fixation were not identified. Unlike other verrucomicrobial methanotrophs, genes encoding for enzymes involved in hydrogen oxidation could not be found. In conclusion, the discovery of this new MAG expands the diversity and metabolism of verrucomicrobial methanotrophs.